Analysis of The Incidence of Uterine Leiomyoma Based on Body Mass Index and Neutrophil-Lymphocyte Ratio - Farma, Aufa Faza Fauzan; Kurniati, Yuni Prastyo (Journal La Medihealtico, 2024)
Leiomyoma is the most common benign uterine tumor in the female with an incidence rate of 70-80%. The cause of these tumors is still unknown, but one of the known causes is that they grow in response to hormonal stimulation. Lymphocytic infiltration in this disease has been identified as an unusual finding. This suggests a potential role for lymphocytes in the development of such tumors. A bibliometric analysis of various sources found minimal research on the Neutrophil-Lymphocyte Ratio (NLR) in uterine leiomyoma, especially in Indonesia. This study analyzed the incidence of uterine leiomyoma based on Body Mass Index (BMI) and Neutrophil-Lymphocyte Ratio (NLR). This study used an observational analytic method with a case-control design. The sampling technique used was consecutive sampling and 129 samples were obtained in the form of 65 uterine leiomyoma case groups and 64 adenomyosis control groups. BMI variable parameters were obesity (>25kg/m2) and not obese (≤25kg/m2), while NLR was at risk (>3.53) and not at risk (≤3.53). Data analysis consisted of univariate, bivariate with a Chi-Square test, and continued with multivariate using logistic regression analysis. There was a significant relationship between BMI and uterine leiomyoma incidence (p = 0.028). There was also a significant relationship between NLR and uterine leiomyoma (p = 0.017). NLR had a 3,688-fold more association with the incidence of uterine leiomyoma than BMI. In conclusion, a relationship exists between BMI and NLR in the incidence of uterine leiomyoma. NLR can be a predictor of uterine leiomyoma, especially in women of reproductive age.